Penerapan metode cost plus pricing dengan pendekatan full costing dalam menentukan harga jual pada Gloria Cake and Cookies - Mongula, Jermia; Pusung, Rudy J.; Pinatik, Sherly (Yayasan Widyantara Nawasena Raharja, 2025)
In today's fiercely competitive business world, companies must innovate to stay ahead. The cost-plus pricing method is the simplest way to set a selling price by adding a mark-up or a percentage of expected profit.This study determines the application of the cost-plus pricing method with a full costing approach to determine the selling price of Gloria Cake and Cookies.The study uses qualitative descriptive research. The results show that the cost of production is smaller when using the cost plus pricing method. This is because it does not include detailed factory overhead costs, such as equipment and building depreciation. The full costing method includes all production costs. The results of the calculation of the selling price determination with the expected profit percentage of Gloria Cake and Cookies using the cost plus pricing method with a full costing approach of 12.47% for brudel cake products and 14.05% for marmer cake products resulted in more optimal profits, because all elements of costs incurred have been charged to the selling price of the product.